2010
DOI: 10.1245/s10434-010-1334-3
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the LigaSure and Harmonic Scalpel in Thyroid Surgery: A Single Institution Review

Abstract: Background Over the last few years many surgeons have begun to utilize the LigaSure device or Harmonic scalpel to perform thyroid surgery. Several papers have demonstrated the benefits of these devices over traditional hand-tying techniques. The purpose of this study was to examine our institution’s experience with the LigaSure device and Harmonic scalpel during thyroid surgery and to compare mean operative times and complications associated with each device. Methods A retrospective chart review was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 19 publications
1
37
3
Order By: Relevance
“…Olivier et al detected permanent hypocalcemia in 1 patient and transient hypocalcemia in 21 patients in their series of 100 patients that were operated on through LS in their study (21). Moreover, Zarebczan et al detected transient hypocalcemia in 12 patients in their series of 87 patients that were operated on through LS in their study (22). In contrast, Dionigi et al reported only 1 case of permanent hypocalcemia in 92 patients who underwent HS assisted total thyroidectomy (23).…”
Section: Discussionmentioning
confidence: 93%
“…Olivier et al detected permanent hypocalcemia in 1 patient and transient hypocalcemia in 21 patients in their series of 100 patients that were operated on through LS in their study (21). Moreover, Zarebczan et al detected transient hypocalcemia in 12 patients in their series of 87 patients that were operated on through LS in their study (22). In contrast, Dionigi et al reported only 1 case of permanent hypocalcemia in 92 patients who underwent HS assisted total thyroidectomy (23).…”
Section: Discussionmentioning
confidence: 93%
“…Energy based devices (EBD) have been developed, implemented and increasingly applied in thyroid surgery because they can provide a combined dissection and haemostatic effect (6,7). In particular, advantages of EBD have been described in terms of efficacious haemostasis, reduction of procedure-associated time, reduced incision length, less operative blood loss and transfusion need, decreased postoperative drain, pain and hospital stay (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Some RF-based devices provide electrical current to the vessel followed by an actuated mechanical knife which separates the coagulum into two sealed segments. These devices expedite normally labor-intensive surgical procedures such as lobectomy, 1,2 nephrectomy, 3 gastric bypass, 4-6 splenectomy, 7,8 thyroidectomy, [9][10][11][12][13][14] hysterectomy, 15 and colectomy. [16][17][18][19] However, both electrosurgical and ultrasonic devices have limitations, including the potential for undesirable charring and unnecessarily large collateral thermal damage zones.…”
mentioning
confidence: 99%